Law, regulation, and the promotion of renewable energy in South Africa - Murombo, Tumai (My University, 2016)
Many countries are under pressure to transition from fossil to renewable sources of energy. This pressure comes from multiple points including sustainable energy and climate change imperatives. The energy industry, especially electricity generation, is the main source of greenhouse gases, hence the significance of reductions in this industry. The purpose of this study was to conduct a legal analysis of the renewable energy law in the context of energy law generally in South Africa, to understand the regulatory function of law in promoting renewable energy. The study analysed government legal and policy positions, and the response by non-state actors to such policy positions and laws. Through a qualitative analysis of primary and secondary sources of law and public participation documents, the study found that; while South Africa is committed to renewable energy, its socio-economic, cultural, and environmental context superimposes other priorities that impede progress towards renewable energy. Several obstacles to renewable energy were identified, some internal to energy law and others external to it, coming from other areas such as environmental law, governance, economics, and behavioural sciences. Analysis at the convergence of environmental and energy law revealed misalignment and fragmentation as major obstacles to renewable energy. While barriers are common across the globe, countries cannot apply the same responses with the same results. Regulatory responses, beyond the traditional ‘command and control’ tools are context specific and tools that have worked, in other countries, may not be as effective in South Africa. Socio-economic dynamics determine the legal responses to the barriers to renewable energy or the efficacy of economic incentives to promote renewable energy. However, overall, law and regulation can, and must, play a crucial enabling role by removing barriers to renewable energy. Nevertheless, there are limits to the use law ‘as regulation.’ Renewables will not replace fossil sources yet; rather in the long-term, renewables should become a big part of the energy mix. Despite gaining price competitiveness, it is too early for renewables to displace conventional fossil sources in a context of entrenched structural and institutional obstacles. Concomitant technical, market, economic, and environmental and resource governance interventions are necessary to effectively promote an energy mix substantially composed of renewables. The study recommends that law should create an enabling regulatory environment for renewable energy. South Africa has not used law effectively enough to create this environment, thereby impeding the integration of renewable energy into its energy mix. Aligning energy and environmental law, among other incentives, can enhance this role of law. Legal reforms are necessary to remove the regulatory advantage afforded to conventional sources of electricity and level the playing field.
thesis submitted in fulfilment of the requirements for the degree of DOCTOR OF PHILOSOPHY (PhD) in the School of Law at the University of the Witwatersrand
Keywords: Energy industries--Law and legislation--South Africa; Power resources--Law and legislation--South Africa; Energy policy--South Africa; Sustainable development--South Africa; Environmental law--South Africa